Transversus abdominis plane block and intrathecal morphine use in cesarean section: a retrospective review. Issue 11 (13th September 2019) - Cole, Jacob; Hughey, Scott; Longwell, Jason
Abstract : Objectives: Cesarean delivery is an extremely common surgical procedure practiced worldwide. It is an open abdominal surgery, and is associated with significant postoperative pain. One modality that helps alleviate this pain is the transversus abdominis plane (TAP) block. This analysis sought to evaluate postoperative pain when this block was used in conjunction with intrathecal morphine. Methods: A retrospective review was performed of 142 patients who underwent cesarean section at our institution. Of those, 43 patients had a TAP block performed. The primary outcome for this analysis was the time to first opioid administration following discharge from the operating room. Secondary outcomes included differences in postoperative pain scores, and overall opioid consumption. Results: The average time to first opioid use postoperatively decreased in the TAP group when compared with the No-TAP group, 23.3 versus 12.1, respectively (difference of 48.2% (95% CI 74.0% to 24.3%); p<0.001) and opioid consumption was significantly decreased within the first 24 hours following surgery from 4.55 intravenous morphine equivalents (IVME) to 2.67 IVME, respectively (difference of 107.1% (95% CI 145.1% to 69.2%); p=0.006). Visual analog pain scores were significantly decreased in the TAP group versus the No-TAP group up to 36 hours postoperatively. Conclusions: TAP blocks performed in conjunction with intrathecal morphine may decrease opioid use in the first 24 hours and improve pain scores for at least 36 hours following cesarean section. Because of the favorable safety profile, TAP blocks may contribute meaningfully to multimodal anesthesia for cesarean sections.